Reproductive Biology in the Possible Last Healthy Population of Parodia rechensis (Cactaceae): Perspectives to Avoid Its Extinction - Becker, Rafael (2024)
All 32 Brazilian species of Parodia Speg (Cactaceae) occurring in Rio Grande do Sul Stateare considered threatened, according to the IUCN criteria. Until 2021, Parodia rechensis (CR) wasknown by only two small populations. However, a new population with over 400 individuals wasdiscovered in 2021, prompting the study of its reproductive biology as a way to promote its conservation. Anthesis, breeding system, and natural pollination were studied in the field. The breeding system was studied by applying controlled pollination treatments to plants excluded from pollinators (bagged). Germination features were studied at the Seed Bank of the Porto Alegre BotanicalGarden under controlled temperatures (20, 25, and 30 °C). The anthesis is diurnal and lasts for upto four days. The flowers offer pollen as the sole resource to the pollinators. The study species isunable to set fruit and seed without the agency of pollinators and has self-incompatible (unable toset fruit and seeds when pollinated with pollen of the same individual) characteristics that can considerably restrict its reproduction. Native bees of Halictidae and Apidae (Hymenoptera) are themain pollinators, with a smaller contribution of Melyridae (Coleoptera) and Syrphidae (Diptera).Natural fruit set is moderate (≤64%, per individual), but the species presents vegetative growth,producing several branches from the mother plant. Seeds showed the optimum germination rate at20 °C and an inhibition of 75% in germinability at 30 °C. Our findings suggest the need to managethe species’ habitat to guarantee the permanency of the plants and healthy populations of pollinators as well. Our findings raise concerns about the germination and establishment of new individuals in the context of rising temperatures caused by climate change. Suggestions for the possible management of the extant populations are made.